Aspects of central bank policy making - Eckstein, Zvi. (Berlin ; New York : Springer-Verlag, 1991)
The volume has three parts - the rules and the constraints that are fundamental for central bank policy making; insurance, regulation and safety of commercial banks; and analyses of monetary policies in Germany.
Collection of papers presented at a conference, held January 1990 at the Bank of Israel and Tel Aviv University.
Includes bibliographical references.
Keywords: Banks and banking, Central -- Congresses; Economics